Single-particle imaging without symmetry constraints at an X-ray free-electron laser. (2018) - Rose, Max; Bobkov, Sergey; Ayyer, Kartik; Kurta, Ruslan P.; Dzhigaev, Dmitry; Kim, Young Yong
No abstract available